Long-term movements and activity patterns of platypus on regulated rivers - Tahneal Hawke (Nature Portfolio, 2021)
Abstract The platypus is a semi-aquatic mammal, endemic to freshwater habitats of eastern Australia. There are gaps in the understanding of platypus movement behaviour within river systems, including spatial and temporal organization of individuals. We tracked movements of 12 platypuses on the regulated Snowy and Mitta Mitta Rivers for up to 12-months, the longest continuous tracking of platypus using acoustic telemetry. Platypuses remained relatively localized, occupying 0.73–8.45 km of river over 12 months, consistent with previous tracking studies over shorter periods. Males moved further than females, and larger males had higher cumulative movements, suggesting a possible relationship to metabolic requirements. Platypuses moved greater distances on the Mitta Mitta River, possibly associated with impacts of altered flow regimes to their macroinvertebrate diet. Increased movements and diurnal activity during winter were primarily driven by males, possibly attributable to breeding behaviours, rather than increased costs of winter foraging. Evidence for relatively small movements has implications for declining populations, given areas of localised declines are unlikely to be supplemented by migrating platypuses, especially when dispersal is restricted by dam walls. Understanding platypus movement behaviour is pertinent for their conservation, as water resource development and habitat modification continue to reduce connectivity between populations across their distribution.